L’algoritmo di Poe (e il destino del logos) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
The aim of the article is reasoning on an analogy which may help understand what an algorithm can do and, especially, cannot do. The analogy is given by Poe’s Philosophy of composition, in which, by making reference to his poem The raven, he argues for a singular strategy of composition we may compare with an algorithmic writing. KeywordsAlgorithm, Philosophy of technology, Poe